Pengenalan Kosakata Melalui Media Pembelajaran Wordwall Dengan Game Scrabble Words Pada Anak Usia Dini Di KB Tunas Bangsa Winong Patihan Sidoharjo - Sahda Estinengtyas; Fakhruddin Fakhruddin (Universitas 45 Surabaya, 2024)
The limited competence of an educator has a major influence in determining the quantity and quality of teaching which will ultimately play a role in improving the quality of education. This study aims to describe the process of using wordwall learning media with scrabble words games, the achievement of early childhood outcomes and educators, supporting and inhibiting factors, and how to overcome obstacles. The research method used is descriptive qualitative research. The data collection techniques include interviews, observation, and documentation. Data validity techniques used source triangulation and technique triangulation. Data analysis used the Miles and Huberman analysis model, namely data reduction, data presentation, and conclusion drawing. The results showed that the process of vocabulary recognition through wordwall learning media with scrabble words games in the implementation process was in accordance with the existing components, starting from pre-cycle, cycle 1, which contained planning, action, observation, and reflection. While the achievement of the results of students and educators is classified into normative or relative criteria and absolute criteria. Supporting factors after the use of wordwall learning media with scrabble words games are pictures and vocabulary that make children interested in wanting to learn it. While the inhibiting factor is that the letters in the scrabble media are capitalized which makes it a little difficult for children to find them. Overcoming these obstacles, educators balance capital letters during learning and provide easy vocabulary for students.